Strategies to improve the immunogenicity of prM+E dengue virus type-2 DNA vaccine - Chutitorn Ketloy (2018)
© 2017, Allergy and Immunology Society of Thailand. All rights reserved. Background: An important goal for dengue vaccines is to induce a high and durable level of neutralizing antibody. Objective: Three strategies were investigated for improving the immunogenicity of a prM+E dengue serotype 2 (DENV-2) DNA vaccine: 1) expression in two different plasmids; 2) adjustment of dose; and, 3) introduction of the E sequence of Japanese encephalitis virus (JEV) at the carboxy-terminal portion of DENV-2 E. Methods: Expression cassettes were designed to encode a full-length prM+E sequence of DENV-2 virus employing human-preferred codons (D2prME opt ), or a chimeric prM+E sequence in which the 100-residue carboxy-terminal region of E was derived from JEV (D2prMEJE20 opt ). pHIS and pCMVkan in the presence and absence of CpG motif, respectively, were used for cassette expression. The immunogenicity was compared in mice. Results: Three injections of full-length-D2prME opt in pHIS and pCMVkan induced a comparable neutralizing antibody titer at post-week-2-injection and post-week-4-injection. The 100-μg DNA dose induced a numerically but not statistically high er neutralizing antibody titer than the 10-µg dose. The chimeric-D2prMEJE20 opt produced higher extracellular prM and E protein levels in transfected Vero cells, but had a tendency to induce a lower neutralizing antibody titer in mice when compared with the full-length-D2prME opt . To optimize the immunogenicity of D2prME opt -DNA candidate, both expression plasmids can be used to generate reproducible high neutralizing titer. A higher dose of DNA immunogen may induce a higher neutralizing antibody response. Conclusion: The strategy of the C-terminal region chimeric counterpart with JE20 did not improve but may have reduced the induction of neutralizing antibodies.